The Geopolitical Implications of NATO’s Enlargement in The Nordic Region: The Accession of Finland and Sweden 2022 A Case Study - Jaber , Hasan Mahmoud; Al Momani , Hasan Mohammad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to examine and analyse the geopolitical implications of NATO’s enlargement in the Nordic region through the accession of Finland and Sweden. Methods: Utilising the case study method, this study describes analyses and attempts to predict the phenomenon of NATO’s enlargement through the membership of Finland and the prospected accession of Sweden to NATO. This method enables the researchers to provide an in-depth investigation and understanding of the correlation between different variables and dynamics that influenced NATO’s enlargement in the Nordic region and the geopolitical implications of this enlargement. Results: The accession of Finland and Sweden to NATO carries significant geopolitical implications, which establishes NATO’s preponderance in the Nordic region and encircles Russia’s vital sphere. This turning point represents an extensive strategic challenge for Russia, as it doubles the common borders to approximately 2,500 km. Conclusion: This study concludes that Finland and Sweden’s accession to NATO marked a turning point in the geopolitical, security and balance of power landscape in the Nordic region. Furthermore, the enlargement of the common borders between NATO and Russia will lead to a new interaction pattern, with increased chances of unintentional military skirmishes. Moreover, despite the democratic policies held by Finland and Sweden, the Realpolitik approach in foreign affairs remains most appropriate for security and survival. Eventually, the study emphasises the importance of classical geopolitical assumptions and the significance of the Realism paradigm in interpreting international relations and issues.